What older adults and their caregivers need for making better health-related decisions at home: a participatory mixed methods protocol - France Légare; Simon Décary; Claudia Lai; Paul Holyoke; Karine V Plourde (BMJ Open)
Introduction Shared decision making is an interpersonal process whereby healthcare providers collaborate with and support patients in decision-making. Older adults receiving home care need support with decision-making. We will explore what older adults receiving home care and their caregivers need for making better health-related decisions.Methods and analysis This two-phase sequential exploratory mixed methods study will be conducted in a pan-Canadian healthcare organisation, SE Health. First, we will create a participant advisory group to advise us throughout the research process. In phase 1 (qualitative), we will recruit a convenience sample of 15–30 older adults and caregivers receiving home care to participate in open-ended semi-structured interviews. Phase 1 participants will be invited to share what health-related decisions they face at home and what they need for making better decisions. In phase 2 (quantitative), interdisciplinary health and social care providers will be invited to answer a web-based survey to share their views on the decisional needs of older adults and their caregivers. The survey will include questions informed by findings from qualitative interviews in phase 1, and a workbook for assessing decisional needs based on the Ottawa Decision Support Framework. Finally, qualitative and quantitative results will be triangulated (by methods, investigator, theory and source) to develop a comprehensive understanding of decision-making needs from the perspective of older adults, caregivers and health and social care providers. We will use the quality of mixed methods studies in health services research guidelines and the Checklist for Reporting the Results of Internet E-Surveys checklist.Ethics and dissemination Ethics approval was obtained from the research ethics boards at Southlake Regional Health Centre and Université Laval. This study will inform the design of decision support interventions. Further dissemination plans include summary briefs for study participants, tailored reports for home care decision makers and policy makers, and peer-reviewed publications.Trial registration number NCT04327830.